Предмет: Алгебра,
автор: oksanaperelygi
упростите выражение
(у-3)(у²+3у+9)-у(у-4)(у+4)
Ответы
Автор ответа:
0
(У-3)(у^2+3у+9)-у(у-4)(у+4)=у^3+3у^2+9у-3у^к-9у-27-у^3+4у^2-4у^2+16у=-27+16=-11
Автор ответа:
0
у³-27-у(у²-16)=у³-27-у³+16у=16у-27
т к первые 2 скобки разность кубов а 2 вторые разность квадратов
т к первые 2 скобки разность кубов а 2 вторые разность квадратов
Похожие вопросы
Предмет: Геометрия,
автор: vikaparij8
Предмет: Алгебра,
автор: alenahramcova14
Предмет: Физика,
автор: kylpan1970
Предмет: Физика,
автор: mariaygrigori
Предмет: Математика,
автор: azjdjkcom